THE FACILITATING STRATEGIES OF PSYCHOPEDAGOGY IN THE LEARNING PROCESS - Zanotto Bonamigo, Greice (Revista Gênero e Interdisciplinaridade, 2024)
The primary motivation that gave rise to this study was to reiterate that Psychopedagogy plays a crucial role in Education, expanding opportunities for investigation and reflection on the learning process. When analyzing the works of renowned authors such as Grassi (2013), Bossa (2016) and Scoz (2013), it is evident that the role of the institutional psychopedagogue favors the teacher in the search for self-knowledge, in the reconstruction of their subjectivities and in the reflection on their history , existence and needs. This internal journey enables the teacher to trigger significant transformations in their pedagogical practice. Therefore, the purpose of this article is to deepen the understanding of the learning process in the face of the challenges presented by learning disorders, exploring viable strategies for their implementation. For this investigation, several theoretical references were used that highlight the importance of the educational psychologist, his intervening and preventive role, as well as his fundamental contribution to the school environment.